PROFESSIONAL COMPETENCE OF A TEACHER OF FOREIGN LITERATURE: RETROSPECTIVE ANALYSIS OF TRANSFORMATIONS, MODERN STANDARDS AND CHALLENGES - Сафарян, Світлана (SWorldJournal, 2023)
in modern scientific and pedagogical researches,a significant place is given to the analysis of various aspects of the teacherapos;s pedagogical activity,in particular,the formation,development and improvement of his professional competence, which is a